Copper-catalyzed aryl selenylation of 2-bromodifluoromethylbenzo-1, 3-thi(x)azoles with diaryl diselenides. (3rd December 2022) - Xu, Rong-Fu; Liao, Fu-Min; Cai, Ying; Liu, Jin-Biao
Abstract: An efficient method of copper-catalyzed aryl selenylation of 2-bromodifluoromethylbenzo-1, 3-thi(x)azoles with diaryl diselenides was described to prepare gem -difluoromethylene moiety linked aryl seleno compounds. Under the optimized conditions, various 2-bromodifluoromethylbenzo-1, 3-thi(x)azoles can be coupled with a range of diaryl diselenides to give their corresponding Se -containing gem -difluoroalkyl products in moderate to excellent yields. Graphical abstract: Image 1